Forensic storage framework development using composite logic method - Helmi Rachman; Bambang Sugiantoro; Yudi Prayudi (ILKOM Jurnal Ilmiah, 2021)
Increasing number of information technology users allows possibility for crimes to take advantage of information technology to continue increasing either directly and indirectly. Criminals often use computer devices to commit crimes. This is a major concern so that the need for handling digital evidences becomes significantly urgent. Therefore, a forensic storage framework is required for managing digital evidences. This framework is designed by applying the composite logic method to determine role model of each variable or the initial pattern of the stages to be collaborated. Composite logic produces a role model that is to generate patterns in order to achieve the same goal. This method collaborates framework for handling the pre-existing hdd, ssd, and vmware to be in turn combined into a forensic storage framework. Based on the results of the test, this study proposes a new framework called forensic storage framework which comprises of four main stages, namely preparation, collection, analysis and report. The advantage of this framework is that it can be used to handle digital evidences in four storages which are SSD, HDD, VmWare, and cloud.